2021
DOI: 10.1159/000515718
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas-Preserving Total Duodenectomy: A Systematic Review

Abstract: <b><i>Background:</i></b> The management of the pancreas in patients with duodenal trauma or duodenal tumors remains a controversial issue. Pancreas-preserving total duodenectomy (PPTD) requires a meticulous surgical technique. The most common indication is familial duodenal adenomatous polyposis (FAP). The aims of this study are to carry out a systematic review of the literature on the indications for PPTD and to highlight the risks and benefits compared with other more aggressive proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Some surgeons may think that PPTD is a difficult procedure, but it has been accepted internationally as less invasive for duodenal tumors because it does not include resection of the pancreatic parenchyma [42][43][44]. According to Cantalejo-Diaz M et al who systematically reviewed reports of 211 patients who underwent PPTD for various diseases, including familial adenomatous polyposis and neuroendocrine tumors, the mortality rate was less than 1.4% [45]. In our series of PPTD for 10 patients with MEN1 and gastrinomas, the mortality rate was 0% and the morbidity rate was less than 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons may think that PPTD is a difficult procedure, but it has been accepted internationally as less invasive for duodenal tumors because it does not include resection of the pancreatic parenchyma [42][43][44]. According to Cantalejo-Diaz M et al who systematically reviewed reports of 211 patients who underwent PPTD for various diseases, including familial adenomatous polyposis and neuroendocrine tumors, the mortality rate was less than 1.4% [45]. In our series of PPTD for 10 patients with MEN1 and gastrinomas, the mortality rate was 0% and the morbidity rate was less than 10%.…”
Section: Discussionmentioning
confidence: 99%
“…While the standard treatment for duodenal carcinoma of the second portion is PD, the POPF rate is high (28.9%–38%) and POPF grade C can result in a long hospital stay or mortality. 4 , 7 , 8 This is because patients with duodenal carcinoma are at a high risk of pancreatic fistula as proposed by Callery et al, that is, soft pancreatic gland, small pancreatic duct, high‐risk pathologies such as ampullary and duodenal tumors, and excessive intraoperative blood loss. 9 PPD was reported as an alternative option by Chung in 1995, 10 after which, many case reports and several retrospective studies were published and more than 200 PPDs were reported.…”
Section: Discussionmentioning
confidence: 99%
“… 4 PPD was considered advantageous for preserving pancreatic endocrine and exocrine function, and avoiding hepaticojejunostomy. 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations